Sport Enterpreneur: Usaha Kursus Renang Mahasiswa Pendidikan Olahraga Universitas Muhammadiyah Kalimantan Timur - januar abdilah santoso; Karina Putri Alamanda; Yeni Rahmawati (Jurnal Pesut : Pengabdian untuk Kesejahteraan Umat, 2019)
Swimming course business is one of the business fields in the world of sports that can be cultivated by sports people. This swimming course business is an opportunity that can be taken by students as one of the ways to deal with financial problems. Swimming course business is still wide open for sports students and is still very prospective when viewed from the enthusiasm of the people who are quite high using swimming course services. A superior and competitive swimming course business must have standards in its management system. Standards that must be possessed include competency of the trainer / instructor, adequate learning facilities, good service (service excellent), and effective promotional media. This knowledge will be applied to students of the Muhammadiyah University of East Kalimantan Sports Education to be able to manage their swimming course business well. The results of applying this knowledge are expected to increase the productivity of sports students in developing a swimming course business. So that the independence of sports students in meeting financial problems and funding for college can be helped.